A novel adult plant leaf rust resistance gene Lr2K38 mapped on wheat chromosome 1AL. Issue 3 (10th November 2020) - Sapkota, Suraj; Mergoum, Mohamed; Kumar, Ajay; Fiedler, Jason D.; Johnson, Jerry; Bland, Dan; Lopez, Benjamin; Sutton, Steve; Ghimire, Bikash; Buck, James; Chen, Zhenbang; Harrison, Stephen
Abstract: Soft red winter wheat (SRWW) cultivar AGS 2038 has a high level of seedling and adult plant leaf rust (LR) resistance. To map and characterize LR resistance in AGS 2038, a recombinant inbred line (RIL) population consisting of 225 lines was developed from a cross between AGS 2038 and moderately resistant line UGA 111729. The parents and RIL population were phenotyped for LR response in three field environments at Plains and Griffin, GA, in the 2017–2018 and 2018–2019 growing seasons, one greenhouse environment at the adult‐plant stage, and at seedling stage. The RIL population was genotyped with the Illumina iSelect 90K SNP marker array, and a total of 7667 polymorphic markers representing 1513 unique loci were used to construct a linkage map. Quantitative trait loci (QTL) analysis detected six QTL, QLr.ags‐1AL, QLr.ags‐2AS, QLr.ags‐2BS1, QLr.ags‐2BS2, QLr.ags‐2BS3, and QLr.ags‐2DS, for seedling and adult plant LR resistance. Of these, the major adult plant leaf rust resistance QTL, QLr.ags‐1AL, was detected on all field and greenhouse adult plant tests and explained up to 34.45% of the phenotypic variation. QLr.ags‐1AL, tightly flanked by IWB20487 and IWA4022 markers, was contributed by AGS 2038. Molecular marker analysis using a diagnostic marker linked to Lr59 showed that QLr.ags‐1AL was different from Lr59, the only known LR resistance gene on 1AL. Therefore, the QTL was temporarily designated as Lr2K38 . Lr2K38‐ linked marker IWB20487 was highly polymorphic among 30 SRWW lines and should be useful for selecting the Lr2K38 in wheat breeding programs.